The Role of Social Media in Providing Support for Individuals with Spinal Cord Injury - Fizzotti, Gabriella (British Journal of Healthcare and Medical Research, 2024)
Introduction: New media has changed the dynamics and rules of social interaction, notably doctor-patient communication, which has become transversal. Blogs, Social Networks, Forums and Online Health Communities are increasingly prevalent, allowing patients and their families to discuss issues and questions related to chronic disability conditions. Aim: we evaluated the opportunities offered by the New Media overcoming disability. Material Method: we considered two patients presenting spinal cord injuries (SCI) Both individuals refused the diagnosis and the therapeutic limits related to the spine damage. Results: New media can improve disability self-awareness. Conclusion: technology is a valuable asset, a significant resource; but high technology in medicine cannot replace the high touch that is human contact.